Development of a high-throughput genotyping assay for detection of functional polymorphisms involved in homocysteine metabolism and the methylation process implicated in multiple sclerosis - Davis, William Henry (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMedSc)--Stellenbosch University, 2013.